Navigating the new normal of business with enhanced human resources management strategies - Aquino, Perfecto Gatbonton, Jr., 1962-; Jalagat, Revneio Cabanilla, Jr., 1978- (Advances in human resources management and organizational development (AHRMOD) book series., 2022)
"This book presents effective strategies in human resources management in most organizations worldwide with the end view of shedding light and ideas on how have the existing organizations managed to continue their operations in a new normal operation of the business as they devise/enhance their human resource management strategies amid Covid 19 and its known variants"--